International city tourism : analysis and strategy - Maier, Gunther.; Mazanec, Josef A.; Wober, Karl.; Grabler, Klaus. (Pinter, 1997)
This book is divided into six parts: Local tourism organizations in European cities; An urban tourism database; Analysing and monitoring demand on the disaggregate level; Urban destinations under competitive pressure; Strategic market evaluation; and Exploiting new media: city tourism and the data highway.